User eXperience em startups de software: um paralelo da literatura com a prática diária - Saad, Jullia Gabriella de Oliveira (Universidade Federal de São Carlos, 2021)
Startups are companies designed for a new product or service and that aim to grow quickly in an uncertain environment, highly reactive, and often facing a lack of resources. Software startups face difficulties in incorporating software development processes into their daily activities. Among these difficulties is the adoption of User eXperience (UX) practices. Startups have a constant search for a scalable and sustainable business model and the UX practice helps this business model to be aligned with the needs of real users. Therefore, UX practices can bring benefits to startups even before product development begins. The aim of this project was to bring an updated perspective on what exists in the scientific literature and in practice related to UX in startups, elucidating what are the startups' needs in relation to UX work from a practical point of view. To achieve this objective, the research method was divided into 2 stages: (i) a survey of the literature was carried out, and, through a Thematic Analysis, it was possible to consolidate a set of themes that express previously dispersed knowledge in the literature. It also contributed with a set of open questions gathered from the literature and new questions that emerged from the analysis. These questions helped to outline the studies carried out in the next step. (ii) Field studies were carried out in two startups, from the analysis it was possible to identify needs related to UX that the startups have. It was observed that not always the way to practice UX in startups is to hire a UX professional, small daily actions such as collecting and documenting user feedback can improve the user experience. It was also observed that startups have a lot of data about their users and the use of their product. However, this knowledge is dispersed in various sectors of the company making startups have difficulty in knowing how to use this data. From the results obtained in these two stages, a parallel between literature and practice was outlined. The parallel brings a new starting point for future studies related to UX in startups.
User eXperience in software startups: a parallel between literature and daily practice
Keywords: UX; Experiência do usuário; User experience; Startups; Start-ups; Software startup; Análise temática; Thematic analysis; Mapeamento sistemático da literatura; Systematic mapping study; Estudos na indústriia; Studies in industry; Startup de software; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::SISTEMAS DE COMPUTACAO